2019
DOI: 10.12659/msm.913026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Recent Trends in Research on Vitamin D: A Quantitative and Co-Word Analysis

Abstract: BackgroundIn recent years, many studies on vitamin D have been published. We combed these data for hot spot analyses and predicted future research topic trends.Material/MethodsArticles (4625) concerning vitamin D published in the past 3 years were selected as a study sample. Bibliographic Items Co-occurrence Matrix Builder (BICOMB) software was used to screen high-frequency Medical Subject Headings (MeSH) terms and construct a MeSH terms-source article matrix and MeSH terms co-occurrence matrix. Then, Graphica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 38 publications
3
21
0
1
Order By: Relevance
“…Cluster analysis of these words based on co-occurrence frequency can reflect the association between multiple words [36]. Co-occurrence of keywords was considered to be the main approach for identifying research themes and knowledge structure by displaying the relationship between keywords [37]. This study used the co-occurrence analysis and clustering analysis methods to study the relationship between multiple questions from patients with hypertension on the internet.…”
Section: Co-occurrence Analysis and Clustering Analysismentioning
confidence: 99%
“…Cluster analysis of these words based on co-occurrence frequency can reflect the association between multiple words [36]. Co-occurrence of keywords was considered to be the main approach for identifying research themes and knowledge structure by displaying the relationship between keywords [37]. This study used the co-occurrence analysis and clustering analysis methods to study the relationship between multiple questions from patients with hypertension on the internet.…”
Section: Co-occurrence Analysis and Clustering Analysismentioning
confidence: 99%
“…In the light of the evidence from various groups regarding the beneficiary effect of these vitamins, we investigated their interaction with the Spike protein. There are two forms of vitamin D—cholecalciferol (vitamin D3) and ergocalciferol (vitamin D2) [ 44 ]. Here, we found that vitamin C (∆G = −2.95 kcal/Mol) and vitamin D3 (∆G = −5.52 kcal/Mol) can directly interact with the Spike protein of SARS-CoV-2 ( Table S3 ), which further reaffirmed the possibility of their use as a drug for the treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of LVC de-implementation on the patient experience may be service-speci c. In the present survey, not receiving LVC-vitamin D resulted in a greater impact to the patient-clinician relationship than the three other services. While this nding may be associated with the popularity of vitamin D in the scienti c literature and popular media, 45,46 further research on variation in patient-reported outcomes in response to de-implementation at the service level is needed.…”
Section: Discussionmentioning
confidence: 99%